(untitled) (Research, Society and Development, 2020)
This work addresses the execution of the UEPB campus-VIII PEX CANNABIS extension project, a theme using digital tools, on the use of medical cannabis and its therapeutic applications. This is a descriptive study, like an experience report carried out remotely, under a pandemic scenario, by extension students from the Dentistry course at the State University of Paraíba (UEPB) in 2020. The activity plan was planned from consecutive meetings on platforms such as Google Meet® and Zoom®, configuring the schedule and the subsequent execution of actions, such as cine-debate, presentation of theoretical seminars, conducting polls, posts and scientific publications, as well as events held over lifetimes. The weekly publication of informative schemes on Therapeutic Cannabis and its applicability was made, obtaining an increased level of likes, comments, submissions, among other forms of interaction; online cine-debate, national and international contacts. It was observed that, after carrying out the activities, there was a satisfactory result in terms of interactivity by a wide audience and dissemination of the topics provided, providing scientific and didactic knowledge.